2001
DOI: 10.1097/00005373-200110000-00005
|View full text |Cite
|
Sign up to set email alerts
|

A New Cervical Spine Clearance Protocol Using Computed Tomography

Abstract: In our series, the selective use of helical CT scanning with plain radiography increased the accuracy with which cervical spine injury was detected from 54% to 100%. The protocol allowed for more rapid evaluation in many patients as well. We recommend that practice guidelines include the use of helical CT scan of the entire C-spine as the diagnostic procedure for those blunt trauma patients undergoing CT scanning of the head.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(62 citation statements)
references
References 14 publications
3
57
0
2
Order By: Relevance
“…Much of the literature focuses on the specific utility of different radiologic modalities. Several studies have indicated that helical CT alone is sufficient to detect cervical spine injuries [5,18]. Others have recommended the use of MRI acutely to detect ligamentous injuries, as they found that 60 % of flexion extension films are inadequate, consistent with the findings in our patient population [10].…”
Section: Discussionsupporting
confidence: 76%
“…Much of the literature focuses on the specific utility of different radiologic modalities. Several studies have indicated that helical CT alone is sufficient to detect cervical spine injuries [5,18]. Others have recommended the use of MRI acutely to detect ligamentous injuries, as they found that 60 % of flexion extension films are inadequate, consistent with the findings in our patient population [10].…”
Section: Discussionsupporting
confidence: 76%
“…However, with little further effort, the incidence of missed cervical spine and ligamentous injuries could be consistently decreased to fractions of a percent [10,123,127,128,147,150]. Among 15 injuries from 887 dynamic examinations, five could have been detected by plain films and CT, and a further proportion (possibly as high as 71%) detected by entire cervical spine CT. By performing plain films and high resolution entire cervical spine CT scans, the incidence of missed unstable injuries may be reduced to less than 8 ⁄ 887 (0.9%) and possibly to 2-3 ⁄ 887 (0.2-0.3%).…”
Section: Dynamic Fluoroscopymentioning
confidence: 97%
“…In one series, had entire cervical spine CT been omitted while patients were unconscious, three cervical injuries at C2, C5 and C6 ⁄ C7 would have been missed [125]. No cervical spine injuries were missed following 158 entire CT scans in combination with plain films [147]. Entire CT may represent a minimum standard once an injury is detected because 10-31% of cervical fractures have associated non-contiguous fractures [148,149].…”
Section: Computerised Tomographymentioning
confidence: 99%
See 2 more Smart Citations